Changing Mortuary Practices in the Southwestern United States and Northern Sonora. Issue 2 (2nd April 2020) - Thiel, J. Homer
Abstract : Excavations within three historic period cemeteries in Tucson, Arizona have revealed changing attitudes toward treatment of the dead during the time span between 1775 and 1909. The ways people buried their family members and friends reflect evolving religious beliefs and the elaboration of mourning rituals. These trends occurred throughout the greater Southwest.